Breast cancer in Portugal: Temporal trends and age-specific incidence by geographic regions. (June 2018) - Forjaz de Lacerda, Gonçalo; Kelly, Scott P.; Bastos, Joana; Castro, Clara; Mayer, Alexandra; Mariotto, Angela B.; Anderson, William F.
Highlights: Age-adjusted breast cancer incidence rates increased in all regions and at all ages. Southern Portugal presented the highest age-adjusted rate. Northern Portugal presented the fastest rate of increase. Women under age 45 years have expressed higher EAPCs than women age 45+ years. Forecasts have shown that Northern rates might soon surpass Southern rates. Abstract: Background: Female breast cancer incidence rates have been increasing in Portugal for years. We, therefore, conducted the first nationwide breast cancer study to assess regional differences. Methods: Cases were obtained from population-based cancer registries covering the country's Mainland (South, North, Centre), as well as the two Autonomous Regions (Azores and Madeira), for the time-period 1998 through 2011. Analyses were restricted to ages 30–84 years and stratified by region. We used the age-period-cohort (APC) framework to complement standard descriptive techniques and to forecast future trends. Estimable APC parameters included net drift, longitudinal age-specific incidence rate curves, and fitted age-specific incidence rate ratios. Results: There were 71 545 breast cancer cases diagnosed in Portugal at ages 30–84 years from 1998 to 2011. The South presented the highest age-standardized rate (155.8/100 000), while the North presented the fastest rate of increase (3.6%/year). Age-specific statistical interactions were observed between regions. Younger women in the North revealed a decreased risk of developing breast cancer compared to women from the same age group in the South and Centre, while that risk was reversed in older women (p < 0.05). We estimate that from 2014 onwards, the North might rank first among all regions. Conclusion: The variant patterns observed could be due to a combination of different screening practices and/or exposure to risk factors across regions. Disease heterogeneity among younger and older women may also explain part of the differences in age-specific rates. These results justify continued monitoring of breast cancer incidence by region.